2021
DOI: 10.1115/1.4049103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combined Hot-Streak and Swirl Profile on Cooled 1.5-Stage Turbine Aerodynamics: An Experimental and Computational Study

Abstract: Recently developed lean-burn combustors offer reduced NOx emissions for gas turbines. The flow at exit of lean-burn combustors is dominated by hot-streaks and residual swirl, which have been shown–individually–to impact turbine aerodynamic performance. Studies have shown that residual swirl at inlet to the high-pressure (HP) stage predominantly affects the vane aerodynamics, while hot-streaks affect the rotor aerodynamics. Studies have also shown that these changes to the HP stage aerodynamics can affect the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 71%
See 1 more Smart Citation
“…However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 71%
“…Although there are several works that presented and discussed the effect of injecting swirl profile [10], hot-streak [11,12] and entropy waves [13,14], to authors knowledge there are no published experimental studies that combine the effects of a swirl profile and unsteady temperature perturbation (EW) in an annular turbine cascade. The only experimental campaign getting close to the present one has been carried out at Oxford university and it is based on the combustor simulator developed in Adams et al [15]: this campaign combines the generation of a swirl profile with a steady temperature perturbation [16]. According to Khanal et al [17] computational study, a superimposition of the isolate cases considering either a swirl profile or a temperature perturbation leads to misleading results, hence they should be considered together, their effects being strongly non-linear.…”
Section: Introductionmentioning
confidence: 94%
“…The time-averaged film cooling effectiveness on the rotor blade SS and PS was reduced by 10% and 6%, respectively with respect to the uniform case. Very recently Adams et al [31] conducted the first joined experimental and CFD investigation on the impact of combined realistic hot-streak and swirl on a 1.5 stage film-cooled turbine. They conducted the experimental measurements on the new research turbine called LEMCOTEC in the OTRF, which has been designed to represent new generation aero-engine operating conditions and architectures.…”
Section: Combined Residual Swirl and Hot-streak Effects On Turbinesmentioning
confidence: 99%
“…The interaction of the combustion chamber with a turbine located downstream is a very important subject for engine manufacturers. Thus, several studies have already been made on various configurations, in particular in order to understand the effects of a hot spot migration in the turbine [12][13][14]. For the FACTOR configuration, many LES of the isolated or integrated chamber with the downstream turbine are already available in the literature [15][16][17][18][19][20][21].…”
Section: Combustion Chamber/turbine Integrated Simulationmentioning
confidence: 99%